2020
DOI: 10.3390/molecules25225336
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Provocation by Different Nanoparticles: An Innovative Approach to Manage the Cancer and Other Common Diseases

Abstract: A proper execution of basic cellular functions requires well-controlled homeostasis including correct protein folding. Endoplasmic reticulum (ER) implements such functions by protein reshaping and post-translational modifications. Different insults imposed on cells could lead to ER stress-mediated signaling pathways, collectively called the unfolded protein response (UPR). ER stress is also closely linked with oxidative stress, which is a common feature of diseases such as stroke, neurodegeneration, inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 273 publications
0
26
0
Order By: Relevance
“…This might have significant implications on the entry of SARS-Cov2 inside host cells. SARS-CoV-2 preferentially infects and propagates alveolar type II cells that are the precursor of gas exchanging [ 112 ], and curcumin has reportedly protected alveolar type II cells of the inflammatory lung [ 113 ]. It could be assumed that curcumin has the potential to be effective against SARS Cov-2 but, its limited oral bioavailability is a snag in its handiness.…”
Section: Polyphenolsmentioning
confidence: 99%
“…This might have significant implications on the entry of SARS-Cov2 inside host cells. SARS-CoV-2 preferentially infects and propagates alveolar type II cells that are the precursor of gas exchanging [ 112 ], and curcumin has reportedly protected alveolar type II cells of the inflammatory lung [ 113 ]. It could be assumed that curcumin has the potential to be effective against SARS Cov-2 but, its limited oral bioavailability is a snag in its handiness.…”
Section: Polyphenolsmentioning
confidence: 99%
“…S7). Previous studies showed that ER stress can be induced by ATP deprivation and gold-based nanoparticles [21,56,57]. In ER-stressed cells, Ca 2 + released from the ER is taken up by mitochondria and subsequently induces mitochondrial Ca 2+ overload, eventually leading to mitochondrial oxidative stress and dysfunction [15,20].…”
Section: Ampli Cation Of Oxidative Stress By Inducing Mitochondrial Dysfunction and Potent Er Stressmentioning
confidence: 99%
“…As a player in the redox balance, endoplasmic reticulum (ER), exerts an essential role in protein synthesis/folding [20], which is prone to be in uenced by extracellular stimuli and changes in intracellular homeostasis [21]. Studies indicated that any alteration of redox homeostasis in the ER would induce ER stress, which could, in turn, promote the generation of ROS [15,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their intrinsic ER stress-inducing capacity, several nanoparticles, including silver, zinc oxide, and iron oxide nanoparticles (Fe 3 O 4 NPs), may be promising alternatives for promoting ER stress at the tumor site. 7 In addition to acting as targeted nanocarriers, these nanoparticles tend to disrupt the balance of the redox state inside the ER lumen, thereby disturbing protein folding and elevating ER stress. 8 Among these nanoparticles, the widely used dual enzyme-mimic nanocatalyst Fe 3 O 4 NPs are able to conduct tumor-specific redox targeting by utilizing the different metabolic environments between the tumor and normal tissues.…”
Section: Introductionmentioning
confidence: 99%